Maximum entropy method for valence quark distributions in exotic hadrons: a study of the $$Z_c(3900)$$ Z c ( 3900 ) case - Chengdong Han; Wei Kou; Xiaopeng Wang; Xurong Chen (European Physical Journal C: Particles and Fields)
Abstract In this study we demonstrate the application of the maximum entropy method (MEM) to determine the valence quark distribution of exotic hadrons. Our investigation yields three key findings. Firstly, we observe a significant shift towards smaller Bjorken scale x in the peak position of the valence quark distribution for hadrons with an increasing number of valence quarks, consistent with previous results by Kawamura and Kumano. Secondly, assuming that the $$Z_c(3900)$$ Z c ( 3900 ) initially consists of four valence quarks, we employ MEM to determine its initial valence quark distribution, estimating a radius of $$r_c=1.276$$ r c = 1.276 fm at an extremely low resolution scale $$Q^2$$ Q 2 . Furthermore, we identify a notable discrepancy between our computed charge form factor $$G_c(q)$$ G c ( q ) at leading order and the outcomes of hadron molecular state calculations. We propose that this form factor can be extracted from the QCD counting rule cross-section, which is grounded in generalized distribution amplitudes (GDA) linked to the multi-quark states.